Assessing the role of SH3RF1 and SH3RF2 polymorphisms in susceptibility to tuberculosis: A case-control study in the Han Chinese population. (March 2021) - Chen, Hao; Zhou, Juan; Jiao, Lin; Song, Jiajia; Zhong, Huiyu; Zhao, Zhenzhen; Meng, Zirui; Lu, Xiaojun; Chen, Xuerong; Zhang, Wei; Ying, Binwu
Abstract: Background: Tuberculosis (TB) remains a major public health problem. SH3RF1 and SH3RF2 are candidate genes with multiple single-nucleotide polymorphisms (SNPs) that have the potential to participate in Mycobacterium infection via activation of the JNK signaling pathway. In this case-control study, we aimed to investigate the association of five SH3RF1 and SH3RF2 SNPs with susceptibility to TB in the Western Chinese population. Methods: A total of 900 TB patients and 1534 healthy control subjects were enrolled in our study. All samples used were obtained from the Bio-Bank of resources of Tuberculosis Research in the Department of Laboratory Medicine, West China Hospital, Sichuan University, China. SNP genotyping was conducted using a commercial custom-by-design 2 × 48-Plex SNPscan Kit. Results: The rs758037 variant of the SH3RF2 gene was found to be associated with decreased TB risk based on allelic effects (p = 0.00001, OR = 0.731, 95% CI = 0.641–0.833) and three genetic models (padd = 0.00001, pdom = 0.0003, prec = 0.0007) after the data were controlled for age and gender and underwent Bonferroni correction. The rs4913057 variant of the SH3RF2 gene was found to be associated with increased TB risk in a dominant model (p = 0.021, OR: 1.260, 95% CI: 1.065–1.490). No significant association was observed between other SNPs and TB risk. Conclusion: These findings indicate that polymorphisms in the SH3RF2 gene are involved in susceptibility to TB in the Western Chinese population. Highlights: SH3RF1 and SH3RF2 are candidate genes that has the potential to participate in Mycobacterium infection. This is the first study that investigated the association of SH3RF1 and SH3RF2 polymorphisms with tuberculosis. SH3RF2 gene are involved in susceptibility to tuberculosis in the Western Chinese population.